Pengolahan Limbah Cair Tahu dengan Metode Adsorpsi Menggunakan Fly Ash dan Bottom Ash dalam Menurunkan Parameter Amonia - Badu, Risti Ristianingsih; Umadji , Nur Inda R.; Ibrahim , Sri Rahmi I.; A. MS. A, Anisyah (Department of Environmental engineering, Faculty of Science and Technology, Islamic State University Sunan Ampel Surabaya, 2024)
Tofu production wastewater contains ammonia which causes problems for aquatic organisms and health issues for humans. The reduction of ammonia levels in tofu wastewater can be achieved using the adsorption process with adsorbent materials such as fly ash and bottom ash. The aim of this research is to identify the effectiveness of fly ash and bottom ash in the adsorption process of ammonia pollutants in tofu wastewater. In this study, each sample was treated with control, 25 grams of fly ash, 50 grams of fly ash, 75 grams of fly ash, 25 grams of bottom ash, 50 grams of bottom ash, and 75 grams of bottom ash. Subsequently, the fly ash and bottom ash were prepared and then activated using sulfuric acid. The reduction of ammonia with fly ash reached 22% at 25 gr, 42% at 50 gr, and 51% at 75 gr. Meanwhile, bottom ash reduced ammonia by 12% at 25 gr, 40% at 50 gr, and 44% at 75 gr. from the ammonia testing results on tofu wastewater, it was found that both fly ash and bottom ash can reduce ammonia levels, but fly ash is more effective than bottom ash.